APPROACHES TO EDUCATIONAL QUALITY ASSESSMENT: THE EUROPEAN CONTEXT - Liudmyla Zagoruiko (Pavlo Tychyna Uman State Pedagogical University, 2018)
Characteristics of different approaches to the educational quality assessment in the European countries in the light of educational changes had been analyzed in the article. Contradictions had been distinguished taking into consideration the management of the education quality at the institutional level. The processes taking place in the national and world economy lead to domination of the role of educational quality in ensuring the university competitive-ness. The following fundamental processes had been considered: increasing the supply of educational services over demand; the need for the fullest satisfaction of existing and potential consumer inquiries; dominance of quality of educational services in the system of indicators of the university's competitiveness; implemen-tation of innovative educational technologies. Based on the UNESCO programme document it was possible to define three criteria for the quality of educational activities: the quality of the staff, which is determined by the degree of academic qualification of lecturers and research staff of universities; quality of student training; the quality of the infrastructure and the «physical learning environment» of higher education institutions, covering the «whole set of conditions» of their functio-ning including computer networks and modern libraries. The reasons for the formation of accreditation systems had been mentioned. It was noted that accreditation is characterized by the presence of a two-stage proce-dure: one organ (agency) conducts an examination and makes certain conclusions, another one (collegium or council) makes the final decision.  Strategies of internal and external quality assessment had been analysed. The author characterized two approaches to quality assurance: programme-oriented and institutional-oriented approaches.